Interpersonal Relationship and Its Effect on Treatment Compliance in Patients with Type-2 Diabetes Mellitus - Renaldi, Fransiskus Samuel; Riyadina, Woro; Qamar, Muhammad; Sauriasari, Rani (UI Scholars Hub, 2021)
Type-2 diabetes mellitus has become a chronic disease that can lead to serious complications and can only be prevented by compliant treatment of the patients. Compliance can be influenced by various factors, one of which is interpersonal factors. This study aimed to identify various interpersonal relationship problems between patients and healthcare workers that can affect their treatment compliance behavior. This study employed a qualitative design with phenomenological methods. This research was conducted in Central Bogor City in March-August 2020. The data were collected by conducting in-depth interviews with 20 type-2 diabetes mellitus patients who had been confirmed by the Community Health Center and focus group discussions with 12 healthcare workers consisting of doctors, pharmacists, nutritionists, and nurses. The data were then transcribed and content clouds analysis was carried out. The results showed that most of the patients (76%) followed the advice given by healthcare workers to carry out routine controls. This is a form of patients’ trust in healthcare workers as their health consultants. The trust arises from the convenience of interaction between the two parties. Providing adequate information will increase patients’ understanding and encourage them to take appropriate action for themselves. As many as 12 out of 20 patients chose the Community Health Center for their routine control because the services were sufficient in treating type 2 diabetes mellitus. From this study, it can be concluded that patients tend to comply if they feel trust in the health workers, which arises if they can feel the benefits during their therapy.